High internal inductance for steady-state operation in ITER and a reactor. (26th June 2015) - Ferron, J.R.; Holcomb, C.T.; Luce, T.C.; Park, J.M.; Kolemen, E.; La Haye, R.J.; Solomon, W.M.; Turco, F.
Abstract: Increased confinement and ideal stability limits at relatively high values of the internal inductance ( ) have enabled an attractive scenario for steady-state tokamak operation to be demonstrated in DIII-D. Normalized plasma pressure in the range appropriate for a reactor has been achieved in high elongation and triangularity double-null divertor discharges with at, near the ideal kink stability limit calculated without the effect of a stabilizing vacuum vessel wall, with the ideal-wall limit still higher at . Confinement is above the H-mode level with . At, the current is overdriven, with bootstrap current fraction, noninductive current fraction and negative surface voltage. For ITER (which has a single-null divertor shape), operation at is a promising option with and the remaining current driven externally near the axis where the electron cyclotron current drive efficiency is high. This scenario has been tested in the ITER shape in DIII-D at, so far reaching and at with performance appropriate for the ITER Q=5 mission, . Modeling studies explored how increased current drive power for DIII-D could be applied to maintain a stationary, fully noninductive high discharge. Stable solutions in the double-null shape are found without the vacuum vessel wall at, and, and at with the vacuum vessel wall.